Polymorphisms in TLR4 Gene Associated With Somatic Cell Score in Water Buffaloes (Bubalus bubalis) - Roldan-Montes, Valentina; Cardoso, Diercles Francisco; Hurtado-Lugo, Naudin Alejandro; do Nascimento, André Vieira; Santos, Daniel Jordan de Abreu; Scalez, Daiane Cristina Becker; de Freitas, Ana Cláudia; Herrera, Ana Cristina; Albuquerque, Lucia Galvão; de Camargo, Gregório Miguel Ferreira; Tonhati, Humberto (Frontiers in Veterinary Science, 2020)
Considering the importance of the diseases affecting the productive performance of animals in the dairy industry worldwide, it is necessary to implement tools that help to control and limit the occurrence of such diseases. As the increased somatic cell counts (SCC) are a direct expression of the inflammatory process, they are candidates to become the usual parameter for assessing udder health regarding milk quality and for monitoring mastitis incidences. Toll-Like Receptors are membrane proteins that play a key role in immunity, recognizing pathogens and, subsequently, activating immune responses. The present study was conducted to identify single nucleotide polymorphisms in the TLR4 gene of buffaloes and to analyze its associations with somatic cell counts. DNA samples of 120 Murrah buffaloes were used. The whole coding region of the TLR4 gene was amplified by polymerase chain reaction reactions and sequenced for polymorphism scanning. A total of 13 polymorphisms were identified for the sequenced regions of the TLR4, most of which are in the coding region. The association with the somatic cell score was highly significant (p < 0.001) for all identified polymorphism of TLR4 gene (g.54621T>A, g.54429G>T, g.54407T>A, g.46616C>A, g.46613T>G, g.46612A>G, g.46611C>A, g.46609T>G, g.46541C>G, g.46526C>A, g.46516T>C, g.46376C>T, g.46372T>C). Therefore, it is suggested that the markers of the TLR4 gene can be used as molecular markers for mastitis resistance in buffaloes, due to their association with somatic cell counts.